Associations of Body Mass Index (Maternal BMI) and Gestational Diabetes Mellitus with Neonatal and Maternal Pregnancy Outcomes in a Multicentre European Database (Diabetes and Pregnancy Vitamin D and Lifestyle Intervention for Gestational Diabetes Mellitus Prevention). (12th June 2012) - Vellinga, Akke; Zawiejska, A.; Harreiter, J.; Buckley, B.; Di Cianni, G.; Lapolla, A.; Corcoy, R.; Simmons, D.; Adelantado, J. M.; Damm, P.; Desoye, G.; Devlieger, R.; et al.
Abstract : Objective . Assess the impact of Gestational Diabetes Mellitus (GDM) and obesity on neonatal and maternal pregnancy outcomes. Methods . Cross-sectional data (3343 pregnancies) from seven European centres were included in a multilevel analysis of the association between GDM/obesity and caesarean section, macrosomia and neonatal morbidities. Results . Comparison of databases identified reporting differences between countries due to the inclusion of true population based samples or pregnancies from specialised tertiary centres, resulting in higher prevalences of GDM for some countries. The analysis showed that obesity and GDM were independent risk factors of perinatal complications. Only BMI had a dose-dependent effect on the risk of macrosomia and caesarean section. Both obesity (BMI > 30 kg/m 2 ) and GDM were independent risk factors of neonatal morbidities. Conclusions . Obesity and GDM were independent risk factors of perinatal complications. The effect of the worldwide obesity and diabetes epidemic is extending to the next generation.